1998
DOI: 10.1038/sj.onc.1201494
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of NIH3T3 fibroblasts by the c-Kit receptor tyrosine kinase: effect of receptor density and ligand-requirement

Abstract: Ectopic expression of the normal murine receptor tyrosine kinase, c-Kit, in NIH3T3 cells induced many phenotypic changes characteristic of transformation including anchorage-independent growth, focus formation and tumorigenicity in nude mice. Although transformation was largely dependent on the presence of recombinant murine Steel Factor (SLF), the ligand to the c-Kit receptor, anchorage independent growth did occur at a low frequency in the absence of added factor, and this could not be inhibited by neutralis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 30 publications
3
30
0
Order By: Relevance
“…Only cells expressing the GNNK7 isoform were tumorigenic in vivo with a latency period of approximately 42 days ( Table 1). As previously reported (Caruana et al, 1998), NIH3T3 cells expressing murine GNNK7 c-Kit also induced tumours, in this case with an average latency of 50 days. Table 1 for details) were assayed for focus formation in the presence or absence of SLF.…”
Section: Transformation Of Nih3t3 Cells Expressing C-kit Isoformssupporting
confidence: 86%
See 4 more Smart Citations
“…Only cells expressing the GNNK7 isoform were tumorigenic in vivo with a latency period of approximately 42 days ( Table 1). As previously reported (Caruana et al, 1998), NIH3T3 cells expressing murine GNNK7 c-Kit also induced tumours, in this case with an average latency of 50 days. Table 1 for details) were assayed for focus formation in the presence or absence of SLF.…”
Section: Transformation Of Nih3t3 Cells Expressing C-kit Isoformssupporting
confidence: 86%
“…A representative set of experiments is shown in Table 1; in each case the results were con®rmed in at least one additional experiment. As previously described for human GNNK+ KIT expressed from pRSV009/A+ vector (Caruana et al, 1998), anchorage independent growth was observed in cells expressing both isoforms, and the yield of colonies was lower at high levels of expression. Similar to the previous study, colony formation was substantially independent of added SLF for human but not murine Kit.…”
Section: Transformation Of Nih3t3 Cells Expressing C-kit Isoformssupporting
confidence: 59%
See 3 more Smart Citations